Leisure and aging theory and practice - Gibson, Heather J. (Heather Julie); Singleton, Jerome F. 1950- (Human Kinetics, 2012)
The number and percent of older people in developed countries continue to grow, thanks to medical advances and decreases in fertility and mortality rates. And that means that tomorrow's recreation and leisure professionals will be more challenged than ever to meet the needs of an increasingly older culturally diverse population. Leisure and Aging: Theory and Practice provides students and professionals with a balanced perspective of current knowledge as it presents cutting-edge research from the fields of both gerontology and leisure studies. Written by authors from various disciplines who represent an international who's-who in leisure and aging research, this text: explores theories in leisure and aging; bridges the gap between research and application, arming professionals with tools to navigate diverse cultures; and offers insight into delivery of leisure services in older adult communities and long-term care environments. Each chapter features learning objectives, study questions, case studies, exercises, and relevant readings. The book is supplemented by online ancillaries, including an instructor guide, test package, and a presentation package with photos, illustrations, and tables from the text. Together, the text and online ancillaries help students connect theories and practice as they prepare for future roles in their chosen fields. Leisure and Aging is presented in five sections. Part I introduces global perspectives on leisure and aging, while part II examines the relevance of leisure in an aging context. Part III explores the effects of aging on physical, psychological, social, and spiritual well-being and health. Parts IV and V delve into the role of community in aging and leisure and long-term care and leisure. Written for undergraduate students, professors, and professionals in recreation, leisure, gerontology, and aging, Leisure and Aging provides a wealth of knowledge on various aspects of life for older people and the role of leisure in their lives. The text helps students think critically about a phase of life that seems remote from their own and provides perspective to their understanding of aging and leisure.